Glycolytic reprogramming during microglial polarization in neurological diseases - Li, Xiaoting; Fang, Congcong; Li, Yina; Xiong, Xiaoxing; Xu, Xu; Gu, Lijuan (Frontiers in Immunology, 2025)
BackgroundMicroglia, the resident immune cells of the central nervous system (CNS), play pivotal roles in the onset and progression of various neurological disorders. Owing to their remarkable plasticity, microglia can adopt diverse phenotypic states in response to distinct microenvironmental cues. Over the past decades, accumulating evidence has demonstrated that immune cell metabolism critically regulates their polarization and effector functions through a process termed metabolic reprogramming, in which glucose metabolism is particularly central. Glycolytic reprogramming underlies the entire polarization process, and elucidating its mechanisms may enable targeted modulation of microglial activity to mitigate their deleterious effects in CNS pathologies, thereby offering novel therapeutic avenues for these diseases.Aim of the ReviewThis paper summarizes what is known about microglial polarization and glycolytic reprogramming and explores their important roles in the development of neurological diseases. The link between microglial metabolomics and epigenetics in neurological disorders requires further study.Key Scientific Concepts of the ReviewMicroglia exhibit distinct phenotypic states at different stages of central nervous system (CNS) disorders, and these polarization processes are closely coupled with glucose metabolic reprogramming. Proinflammatory microglia predominantly rely on glycolysis, whereas reparative or anti-inflammatory phenotypes primarily utilize oxidative phosphorylation. Targeting glycolytic pathways to limit the polarization of microglia toward proinflammatory states has emerged as a promising therapeutic strategy for CNS diseases.